KINERJA UNIT PELAKSANA TEKNIS DAERAH PENGUJIAN KENDARAAN BERMOTOR KABUPATEN NGANJUK TAHUN 2014 - Asokawati, Ardiana Nungky; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The purpose of this research is to find out the performance of the Local Technical Implementation Unit (UPTD)Motor Vehicle Testing of Nganjuk District through Value for Money approach. This research is a qualitativeresearch and the object of the research is the Local Technical Implementation Unit (UPTD) Motor VehicleTesting of Nganjuk District about the performance which is stated in the Accountability Report of GovernmentAgency Performance (LAKIP) of 2014. The data collection technique has been done by performing interviewtechnique and documentation whereas the data analysis has been done by using qualitative descriptive approachwhich is carried out by collecting, identifying, describing, analyzing, and making conclusion.Based on the resultof the research, it shows that the Local Technical Implementation Unit (UPTD) Motor Vehicle Testing ofNganjuk District has reached the economic and efficiency level quite well. Although the result of the analysis ofperformance of this agency has already reached, the effectiveness should be directed to success the programs andactivities.Keywords : Value for Money, Economic Performance, Efficiency of the Performance, and Effectiveness of thePerformance.